1981
DOI: 10.1002/eji.1830110106
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the nature and cellular distribution of TLMA — a major rat T axis differentiation antigen Identification as the glycosphingolipid GgOse4Cer (asialo GM1)

Abstract: The recently detected T axis differentiation antigen, which was provisionally designated as T-lymphocyte-macrophage-associated antigen (TLMA) could now be identified as the neutral glycosphingolipid GgOse4Cer (asialo-GM1). TLMA is not only expressed on lymphocytes on the T lineage and on macrophages of the rat, but also on eosinophilic cells. On erythrocytes, the determinants are only detectable after neuraminidase treatment. Within the cell surface of thymic lymphocytes, the antigen determinant is partly mask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
(2 reference statements)
1
6
0
Order By: Relevance
“…Thus, as it is possible to consider the' presence of glycoprotein which cross-reacts with anti-asialo GM1 antibody, it is necessary to visualize asialo GM1 in these myeloid cells. A band corresponding to asialo GM1 was detected in macrophages, as shown previously by a microdetection method (6). This band showed the same migration as asialo GM1 obtained by acid hydrolysis of rat erythrocyte GM1 ganglioside (unpublished data).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, as it is possible to consider the' presence of glycoprotein which cross-reacts with anti-asialo GM1 antibody, it is necessary to visualize asialo GM1 in these myeloid cells. A band corresponding to asialo GM1 was detected in macrophages, as shown previously by a microdetection method (6). This band showed the same migration as asialo GM1 obtained by acid hydrolysis of rat erythrocyte GM1 ganglioside (unpublished data).…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, an unknown ganglioside (indicated by a single star) was detected in granulocytes but not in macrophages, and another unknown glycolipid (indicated by double stars) which was detected in glycolipids of macrophages, was not visualized in glycolipids of granulocytes on thin layer chromatogram under the conditions used in this experiment. were recently characterized as asialo GMl immunologically by absorption of cytotoxic of anti-TLMA antiserum and chemically by a microchemical detection method (6,7). Both results clearly showed that asialo GMl has the character of TLMA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In murine and rat T cells, quantification of neutral GSLs has revealed that the amount of neutral GSLs was higher in peripheral T cells compared to thymocytes. The major neutral GSLs in thymocytes are globosides while asialo GM1 is the most abundant neutral GSL in mature T cells (58, 69, 130, 131). In addition, some unique neutral GSLs, such as Galα1-3(F(2))ASGM1, have been detected in rat thymocytes (110).…”
Section: Biosynthesis and Expression Of Gsls In Naïve And Differentiamentioning
confidence: 99%
“…Antibodies to gangliotetraosylceramide abolished the natural killer activity [5-71 and enhanced the growth of lymphoma in vivo [7]. In the rat this glycolipid has been identified not only on T lymphocytes but on macrophages and eosinophilic cells as well [8,9].…”
Section: Introductionmentioning
confidence: 99%